PENGARUH RATIO LIKUIDITAS, SOLVABILITAS, DAN PROFITABILITAS TERHADAP HARGA SAHAM PADA SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015-2024 - Rika Risniawati; Sawukir Sawukir (CV. KAMPUSA AKADEMIK PUBLISING, 2026)
This study aims to examine the effect of Liquidity (Current Ratio/CR), Solvency (Debt to Equity Ratio/DER), and Profitability (Net Profit Margin/NPM) on stock prices of food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2015–2024 period. The research method used in this study is a quantitative method with a descriptive approach. The population consists of food and beverage sub-sector companies listed on the Indonesia Stock Exchange, with a sample of five (5) companies that meet the sampling criteria. The data analysis techniques employed in this study include descriptive statistics, model selection tests, classical assumption tests, panel data regression analysis, and hypothesis testing. Based on the research results, the Current Ratio (CR) variable partially has a significant effect on stock prices, as evidenced by a t-statistic value of 3.307599 > t-table 2.02129 and a significance value of 0.0018 > 0.05. Meanwhile, the Debt to Equity Ratio (DER) variable in the partial test obtained a t-statistic value of -3.265980 > t-table 2.02129 with a significance value of 0.0021 < 0.05, indicating that the Debt to Equity Ratio (DER) partially has a significant negative effect on stock prices. On the other hand, the Net Profit Margin (NPM) variable partially does not have a significant effect on stock prices, with a t-statistic value < 2.02129 and a significance value of 0.2105 > 0.05. In the F-test, the F-statistic value obtained is 16.97550 > F-table 2.8068 with a significance value of 0.000000 < 0.05. Therefore, it can be concluded that the Current Ratio (CR), Debt to Equity Ratio (DER), and Net Profit Margin (NPM) variables simultaneously have a significant effect on stock prices of food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX), with the results of the coefisient of determination test being 49,45%.